2012
DOI: 10.1080/09583157.2012.731496
|View full text |Cite
|
Sign up to set email alerts
|

Rearing of the fruit fly parasitoidDiachasmimorpha longicaudata(Hymenoptera: Braconidae) on X-ray irradiated larvae ofCeratitis capitata(Diptera: Tephritidae)

Abstract: 2012) Rearing of the fruit fly parasitoid Diachasmimorpha longicaudata (Hymenoptera: Braconidae) on X-ray irradiated larvae of Ceratitis capitata (Diptera: Tephritidae), We evaluated the effects of X-ray irradiation on larvae of Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), with the aim of finding a treatment that prevented adult fly emergence, yet did not adversely affect larval quality as rearing hosts for the parasitoid Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Ichneumonidae). Two experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Larvae of A. obliqua (Macquart), A. serpentina (Wiedemann), and A. ludens (Loew) are routinely gamma rayed for the mass-rearing of tens of millions of parasitoids ( Cancino et al 2009b ), ensuring shipments clean of adult flies. Viscarret et al (2012) and Bachmann et al (2015) showed that C. capitata and A. fraterculus larvae irradiated with X-rays are also suitable for the rearing of D. longicaudata in Argentina. The irradiation of host eggs instead of larvae is an important alternative in the mass-rearing of fruit fly parasitoids ( Cancino et al 2009a ), but little work has been done with Anastrepha spp.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae of A. obliqua (Macquart), A. serpentina (Wiedemann), and A. ludens (Loew) are routinely gamma rayed for the mass-rearing of tens of millions of parasitoids ( Cancino et al 2009b ), ensuring shipments clean of adult flies. Viscarret et al (2012) and Bachmann et al (2015) showed that C. capitata and A. fraterculus larvae irradiated with X-rays are also suitable for the rearing of D. longicaudata in Argentina. The irradiation of host eggs instead of larvae is an important alternative in the mass-rearing of fruit fly parasitoids ( Cancino et al 2009a ), but little work has been done with Anastrepha spp.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence likewise indicates that fruit fly larvae are immunologically compromised, thus radiation can result in a higher percent of parasitoid emergence. Diachasmimorpha longicaudata emergence and females-biased sex ratio increased following exposure of both C. capitata and A. fraterculus hosts to X-ray doses of between 20 Gy and 100 Gy [ 45 , 46 ]. Gamma irradiated C. capitata larvae also supported higher D. longicaudata emergence rates and produced a significantly greater proportion of females [ 66 , 67 ].…”
Section: Physiological Basismentioning
confidence: 99%
“…For example, a dose of 60 Gy applied to 150–200 third instar C. capitata placed in a Petri dish, completely inhibits adult fly emergence, whether or not larvae are immersed in diet. However, adult development and eclosion of ~19,000 larvae in a larger container was not completely suppressed even with a dose 100 Gy [ 45 ]. X-rays have lower penetration than gamma rays [ 43 ] and their efficiency is greatly reduced when larvae are immersed in diet and presented in deep-bodied trays.…”
Section: Optimizing Radiation Dose and Age Of Irradiating Fruit Flmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of irradiation occurs because the hosts are not 100% parasitized, so it is irradiated to prevent larvae that have not been parasitized from emerging, contaminating the release site. For this, irradiating equipment is required, gamma ray irradiators are commonly used (Cancino et al, 2002, Viscarret et al, 2012, but X-rays are used in Costa Rica, since they handle low volumes of production in comparison with Mexico, and the purchase of this type of equipment is much simpler. However, when the equipment is damaged, the spare parts are very expensive and specialized technicians that can repair the equipment in the country is scarce.…”
Section: Introductionmentioning
confidence: 99%